Доля одного рукопису - Буйських, С.Б. (Археологія, 2007)
Йдеться про долю неопублікованої монографії Л.М. Славіна «Ольвія. Нариси її історії та культури», написаної у 50-ті рр. XX ст. Приведена краткая характеристика неопубликованной монографии Л.М. Славина «Ольвия. Очерки ее истории и культуры», написанной в 50-е годы XX ст. и ныне хранящейся в Научном архиве Института археологии НАН
Украины. Несмотря на давность и незавершенность работы, многие ее разделы, освещающие различные стороны политического, экономического, этносоциального и культурного развития Ольвии, и сейчас представляют
большой научный интерес. The item briefly describes an unpublished monograph by L.M. Slavin «Olbia. Studies of its History and Culture»
written in the 50s of 20th c. which nowadays is being kept in the Scientific Archive of the Institute of Archaeology,
NA S of Ukraine. The work remains incomplete; however, despite the fact that it was written a long time ago, many of
its sections covering various aspects of political, economic, ethno-social, and cultural development of Olbia are still
of high scientific interest.